Resource quality determines the evolution of resistance and its genetic basis. Issue 21 (17th September 2020) - Roberts, Katherine E.; Meaden, Sean; Sharpe, Stephen; Kay, Suzanne; Doyle, Toby; Wilson, Drew; Bartlett, Lewis J.; Paterson, Steve; Boots, Mike
Abstract: Parasites impose strong selection on their hosts, but the level of any evolved resistance may be constrained by the availability of resources. However, studies identifying the genomic basis of such resource‐mediated selection are rare, particularly in nonmodel organisms. Here, we investigated the role of nutrition in the evolution of resistance to a DNA virus (PiGV), and any associated trade‐offs in a lepidopteran pest species ( Plodia interpunctella ). Through selection experiments and whole‐genome resequencing, we identify genetic markers of resistance that vary between the nutritional environments during selection. We do not find consistent evolution of resistance in the presence of virus but rather see substantial variation among replicate populations. Resistance in a low‐nutrition environment is negatively correlated with growth rate, consistent with an established trade‐off between immunity and development, but this relationship is highly context dependent. Whole‐genome resequencing of the host shows that resistance mechanisms are likely to be highly polygenic and although the underlying genetic architecture may differ between high and low‐nutrition environments, similar mechanisms are commonly used. As a whole, our results emphasize the importance of the resource environment on influencing the evolution of resistance.